2017
DOI: 10.1038/s41598-017-03282-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil biochar amendment affects the diversity of nosZ transcripts: Implications for N2O formation

Abstract: Microbial nitrogen transformation processes such as denitrification represent major sources of the potent greenhouse gas nitrous oxide (N2O). Soil biochar amendment has been shown to significantly decrease N2O emissions in various soils. However, the effect of biochar on the structure and function of microbial communities that actively perform nitrogen redox transformations has not been studied in detail yet. To analyse the community composition of actively denitrifying and N2O-reducing microbial communities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…Biochar is a carbon-rich solid produced by the pyrolysis of biomass (Harter et al, 2014). Several studies have shown that biochar incorporation into soil can have diverse effects on soil microbial species and communities, soil quality, plant growth and greenhouse gas emissions (Lehmann et al, 2011;Cao et al, 2016;Backer et al, 2017;Harter et al, 2017). Although it has been suggested that biochar could reduce soil N 2 O emissions (Spokas & Reicosky, 2009;Wang et al, 2011;Cayuela et al, 2014;Harter et al, 2016a), the underlying mechanism remains unclear (Taghizadeh-Toosi et al, 2011;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is a carbon-rich solid produced by the pyrolysis of biomass (Harter et al, 2014). Several studies have shown that biochar incorporation into soil can have diverse effects on soil microbial species and communities, soil quality, plant growth and greenhouse gas emissions (Lehmann et al, 2011;Cao et al, 2016;Backer et al, 2017;Harter et al, 2017). Although it has been suggested that biochar could reduce soil N 2 O emissions (Spokas & Reicosky, 2009;Wang et al, 2011;Cayuela et al, 2014;Harter et al, 2016a), the underlying mechanism remains unclear (Taghizadeh-Toosi et al, 2011;Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that a shift in microbial community with biochar amendment occurred and different bacteria have different fractionation factors. Harter et al found that biochar amendment significantly altered N 2 O‐reducing microbial taxa (bacterial genes nosZ encoding for N 2 O reducing enzyme) and were probably responsible for N 2 O suppression in soil. Malghani et al also showed higher abundance of the denitrifying gene nosZ in biochar treatment than in the control, possibly due to the high availability of labile carbon.…”
Section: Discussionmentioning
confidence: 99%
“…However, this has not been investigated so far, although there already are reports indicating that reduced quinone groups (hydroquinones), which are very abundant in carbonaceous materials, can serve as electron donors to achieve N 2 O reduction by denitrifying consortia . N 2 O is a powerful greenhouse gas, which significantly destroys the stratospheric ozone layer and can be released at substantial levels from wastewater treatment plants (WWTP) performing nitrogen removal due to incomplete denitrification . Thus, strategies to prevent its emission to the atmosphere from WWTP are in high demand.…”
Section: Introductionmentioning
confidence: 99%
“…9 N 2 O is a powerful greenhouse gas, which significantly destroys the stratospheric ozone layer and can be released at substantial levels from wastewater treatment plants (WWTP) performing nitrogen removal due to incomplete denitrification. 10,11 Thus, strategies to prevent its emission to the atmosphere from WWTP are in high demand. Considering the information cited above, the main objectives of the present work are the following: (1) Modify AC materials obtained from organic wastes, such as pecan nut (Carya illinoinensis) shell and peach (Prunus persica) stone, employing the technique of cold oxygen plasma to enrich their surface with oxygenated functional groups; and (2) evaluate the obtained carbon materials as electron shuttles to enhance CH 4 production and N 2 O reduction rates in sludge incubations.…”
Section: Introductionmentioning
confidence: 99%